UANG PERSPEKTIF EKONOMI ISLAM - Henry Martin Adriansyah (Program Studi Ekonomi Syariah Fakultas Agama Islam Universitas Pahlawan Tuanku Tambusai, 2023)
In Islamic economics, the motives that influence a person to have money are justified only for transactions and precautions. In Islam, someone having money for speculation is prohibited because money according to Islam is only a medium of exchange and a standard of value, so al-Ghazali argued that trading money with money is prohibited because it will imprison the function of money as a medium of exchange. If money can buy or be purchased with other money, then money no longer functions as a medium of exchange but as a commodity. This is prohibited in Islam. Based on his theory about the function of money as a medium of exchange, Ibn Taymiyah strongly opposed money trading because according to him this action would eliminate the function of money itself. Money in Islam is also something that has a flow concept, not a stock concept, money is always flowing, circulating in society in economic life. The conventional concept of Money Demand for Speculation (Demand for Money for Speculation). The reason for someone's demand for money based on this motive will be more in the nature of making a profit in the forex market.